Wear performance of some phenolic composites with boric acid - Mutlu, I.; Oner, C.; Cevik, I.; Findik, F. (Emerald Group Publishing Limited, 2007)
Purpose - The aim of the research is to investigate wear performance of some phenolic composites with boric acid. Design/methodology/approach - The brake lining which has new formulation has been produced by using various additive materials. Various techniques have been used in the production of brake lining. These phenolic composites were subjected to friction and wear tests under different loads, and changes in the hardness and microstructures were examined. Findings - As a result of this study, the following findings are reported. It was not found a direct proportionality between hardness and wear resistance due to the complexity of composite structure. Heat treatment application changed the microstructure of the brake lining, and increased the hardness and also decreased the density. With the increasing of temperature, the ingredients in the braking pad were affected other due to faster diffusion. On the other hand, hardness of specimen increases due to heat treatment and also specific wear ratio changes. As a filling material, barite was used due to better performance in the environmental conditions. More wear was observed in the bigger powder particles comparing to the smaller ones due to more structural loss. Squealing was heard in fiber un-reinforced brake lining due to more barite content In the present samples, boric acid deports the water and establishing the structural equilibrium. Therefore, these samples supplied higher and stable friction of coefficient. Also, heat treatment supplied a stable friction coefficient. With the increasing of copper powder into specimens, friction coefficient also increased. Heat treatment made the increment of hardness of specimens and also it made effect on the hardness with strengthening bonds of interparticles. Research limitations/implications - Limitations in the present research are as follows: two different pressures and eight different temperatures were used and brake linings were subjected to wear test, hardness tests, microstructures were examined. Practical implications - For future work, instead of buying expensive brake lining, new and cheaper phenolic linings are produced. By this process, economic benefit can be gained and also environmental protection can be succeeded in producing such asbestos free brake linings. Originality/value - This paper fulfills an identified information and offers practical help to the industrial firms working with brake lining and also to the academicians working on wear of materials.
Keywords: friction; wear; acids